ANALISIS DAMPAK LALU LINTAS DARI PUSAT KEGIATAN TERHADAP KEMACETAN LALU LINTAS (Studi Kasus: Jalan Ahmad Yani, Kota Bekasi) (Jurnal Planesa (Planologi), 2016)
Ahmad Yani Road has an important role in supporting the movement of activities in the activities centers along Ahmad Yani Road. This road has a movement that is high enough so that at certain hours, especially during peak hours when leaving and coming home from work or lunch breaks also make the volume of vehicles crossing the road is dense because of the capacity of roads that can not accommodate the volume of passing vehicles. Existing activity centers such as government centers, banks, shophouses (trade and services), hospitals, fasos and fasum (GOR Bekasi) are all on the side along Ahmad Yani Road. This study examines the effect of several centers of activities such as government, banks, shophouses and hospitals against traffic congestion that occurred in Ahmad Yani Road. The approach method used in this study is descriptive, focused on quantitative analysis. And traffic calculation of road capacity and vehicle volume before and after influenced by activity center, as well as the awakening, pull and delay that exist on Ahmad Yani Road that happened at hour which will be done research. The result of the analysis shows that the existing activity center contributes to the pull of traffic volume of 2.50% and 0.91% rise for South to North direction, while for North to South contributes 2.23% and 0.36%. The level of service for the Ahmad Yani Road segment prior to the influx of vehicle entry from the center of activity for the North-North direction is 0.95 after being affected to 0.98. while the service level for North-South direction before was affected by 0.87 after being influenced to 0.91. then based on the Level of Service (LOS) of the Ahmad Yani Road segment is included in category E in the level of road service, with unstable traffic flow characteristics.Â Keywords: ahmad yani road, bekasi city, analysis center activities, traffic congestio